Merger control and its application in Peru: a comparative law perspective - Roca Lizarzaburu, Luis Fernando (2018)
There are as many merger control mechanisms as jurisdictions, each one of them with its own strength and particularities. Such variety can be used to analyze the effectiveness of such techniques, and evaluate their applications in a local scale.In this article, the author reviews some of the principal aspects in which merger control mechanisms differ. Subsequently, and based on the advantages or disadvantages that these mechanisms may show, the author analyzes the characteristics that a merger control mechanism should have for it the be implemented in Perú our country.